Cakes and Candies - Fitchett, Greta (United Kingdom Search Press ltd, 2013)
Twenty projects of stitched, tempting treats, each with simple, step-by-step instructions and beautiful photographs, are included in this delectable sewing book. Fabric and thread are all that is needed to create a wonderful range of sewn confectionary, and once decorated with buttons, ribbons, and beads, they look good enough to eat. Projects include a box of chocolates, a fruit tart, a creamy meringue, cupcakes, and much more, and a section at the front of the book that details basic techniques and materials is also included. These tempting treats are great fun to make and can be used to decorate the home or provide a special and unique gift for a friend or relative
Arts (Cooking)
2 13
NEW
Keywords: Handicrafts, Arts & Crafts; Interior decoration accessories; Needlework